Progress in Therapy Development for Amyotrophic Lateral Sclerosis - Kalina Venkova-Hristova; Alexandar Christov; Zarine Kamaluddin; Peter Kobalka; Kenneth Hensley (Neurology Research International)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that cannot be slowed substantially using any currently-available clinical tools. Through decades of studying sporadic and familial ALS (SALS and FALS), researchers are coming to understand ALS as a complex syndrome with diverse genetic and environmental etiologies. It is know appreciated that motor neuron degeneration in ALS requires active (gain of function) and passive (loss of function) events to occur in non-neuronal cells, especially astrocytes and microglia. These neuroinflammatory processes produce paracrine factors that detrimentally affect motor neurons, precipitating protein aggregation and compromising cytoskeletal integrity. The result is a loss of neuronal homeostasis and progressive die-back of motor axons culminating in death of the afflicted motor neurons. This review will discuss experimental therapeutics that have been tested in murine ALS models, with an emphasis on those that have progressed to human clinical trials. Reasons will be considered for the frequent failure of preclinical successes to translate into positive clinical outcomes. Finally, this review will explore current trends in experimental therapeutics for ALS with emphasis on the emerging interest in axon guidance signaling pathways as novel targets for pharmacological support of neural cytoskeletal structure and function in order to slow ALS.